2010
DOI: 10.1111/j.1365-2966.2010.17207.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing adiabatic contraction with Sloan Digital Sky Survey elliptical galaxies

Abstract: We study the profiles of 75 086 elliptical galaxies from the Sloan Digital Sky Survey (SDSS) at both large (70-700 h −1 70 kpc) and small (∼4 h −1 70 kpc) scales. Weak lensing observations in the outskirts of the halo are combined with measurements of the stellar velocity dispersion in the interior regions of the galaxy for stacked galaxy samples. The weak lensing measurements are well characterized by a Navarro, Frenk and White (NFW) profile. The dynamical mass measurements exceed the extrapolated NFW profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 79 publications
3
76
2
Order By: Relevance
“…We may then apply this IMF result to the full sample if we assume no additional systematic δ IMF -Σ correlation (cf. Schulz et al 2010).…”
Section: Results: Imf and Dm Fraction Trendsmentioning
confidence: 99%
“…We may then apply this IMF result to the full sample if we assume no additional systematic δ IMF -Σ correlation (cf. Schulz et al 2010).…”
Section: Results: Imf and Dm Fraction Trendsmentioning
confidence: 99%
“…iii) Kroupa-IMF stellar mass. According to Schulz et al (2010), within a sphere of radius equal to re, 42% of the total stellar mass is contained.…”
Section: The Stellar Massmentioning
confidence: 99%
“…Interestingly, in an analogous Chandra study of mass profiles in seven elliptical galaxies with either galaxy-scale or group-scale halos (Humphrey et al 2006), the stellar mass-to-K-band luminosity ratio (M /L K ) was found to be consistent with SSP models assuming a Kroupa ( The IMF is also indicated as the most significant source of systematic uncertainty in a recent test of adiabatic contraction using profiles of 75 086 elliptical galaxies from the Sloan Digital Sky Survey (Schulz et al 2009). This study is based on weak lensing observations in the outskirts of the halo and measurements of the stellar velocity dispersion in the inner regions of galaxies for stacked galaxy samples.…”
Section: On the Choice Of Imf And Its Impact On The Best Fitting Massmentioning
confidence: 99%